Pengembangan Produk Industri Rumah Tangga Berupa Eco Enzym Di Dasa Wisma Perdos - Bassaleng, Andi Jiba Rifai; Arifin, Rosmiaty; Butudoka, Zubair; Masiming, Zulfitriah; Arafat, Yasir (Sambulu Gana : Jurnal Pengabdian Masyarakat, 2024)
ABSTRACT Eco-enzyme is a solution of complex organic substances produced by the fermentation process of leftover organic waste, water and molasses. So that organic waste that has been thrown away and is no longer used can be used as an environmentally friendly product. This eco-enzyme solution has a dark brown color and a strong sour aroma. This research focuses on making eco-enzyme solutions from organic waste from fruit and vegetables. The results of this research show that a good eco-enzyme has a dark brown color, a fresh sour aroma typical of fermentation and has a stable pH with a pH of 4.0, indicating that the eco-enzyme produced is acidic which has benefits such as preventing radiation, clearing water channels, cleaning floors, disinfecting organic etc. Keyword : Domestic Indutry, Eco Enzyme, Dasa Wisma.